Enhancing patient safety through effective materiovigilance system: a prospective observational study on adverse events reporting for medical devices in surgical and orthopaedic departments at a multispecialty hospital - C., Dhandapani; I., Sudharson; T., Boobalan (International Journal of Research in Orthopaedics, 2026)
Background: Medical device-associated adverse events (MDAEs) pose serious risks to patient safety, still its underreporting. The Materiovigilance Programme of India (MvPI) was established to systematically monitor and improve the safety of medical devices. The objective of this study was to enhance patient safety by identifying and analyzing adverse events associated with medical devices and to evaluate healthcare professional’s knowledge about materiovigilance. Methods: A 6-month prospective observational study was conducted at Kovai Medical Centre and Hospital, Coimbatore. MDAEs were recorded and classified under MDR 2017 guidelines. Causality, severity, and risk class were analyzed. A structured questionnaires assessed knowledge, perception, and barriers among 121 healthcare professionals. Results: Among 40 MDAEs, 52.5% involved class C (high-risk) devices like orthopaedic implants, all classified as serious. Significant correlation was found between device class and severity (p=0.0001). Causality assessments showed most events were probable or related. Survey results showed 78.5% awareness of MvPI, yet only 34.7% had reported MDAEs. Conclusions: The study emphasizes the need for improved training, simplified reporting procedures, and institutional support to enhance materiovigilance. Strengthening MvPI with user-friendly tools, confidentiality measures, and feedback systems is crucial to ensuring safe medical device usage.